Governing informality: Drivers of service provision in Nigeria's food wholesale markets - Resnick, Danielle; Liverpool-Tasie, Lenis Saweda O.; Chugh, Aditi (SSRN, 2025)
How does governance affect service provision in Nigeria's wholesale food markets? Sufficient services, such as water, waste collection, and toilet access, are essential for enhancing the safety of healthy and nutritious foods, such as vegetables and fish, and improving the welfare of those who depend on informal trade for their livelihoods. However, these are often substandard in many informal markets, exposing traders and consumers who rely on such markets to higher levels of foodborne hazards and undermining the efficacy of other food safety interventions. Using data from 299 wholesale markets across seven states and the Federal Capital Territory of Nigeria, this paper examines how four governance mechanisms-incentives, information, authority, and capacity-are associated with five services: waste collection, market toilet access, water provision, electricity, and security. We find that having an elected, rather than appointed, market chairperson positively influences waste collection and provision of security. By contrast, larger utility investments, such as water and electricity, are less influenced by governance structures within the markets. Markets located in local government areas (LGAs) under appointed rather than elected governments are associated with worse performance across all services, demonstrating that efforts to address market service delivery need to be embedded in a holistic understanding of multi-level governance dynamics. The findings emphasize that improving food safety and traders' welfare via better service delivery requires empowering stakeholders in informal market governance who not only hold the authority to deliver a diverse set of services but also possess the political incentives to do so.